A whole‐genome, radiation hybrid mapping resource of hexaploid wheat. (April 2016) - Tiwari, Vijay K.; Heesacker, Adam; Riera‐Lizarazu, Oscar; Gunn, Hilary; Wang, Shichen; Wang, Yi; Gu, Young Q.; Paux, Etienne; Koo, Dal‐Hoe; Kumar, Ajay; Luo, Ming‐Cheng; Lazo, Gerard; et al.
Summary: Generating a contiguous, ordered reference sequence of a complex genome such as hexaploid wheat (2n = 6x = 42; approximately 17 GB) is a challenging task due to its large, highly repetitive, and allopolyploid genome. In wheat, ordering of whole‐genome or hierarchical shotgun sequencing contigs is primarily based on recombination and comparative genomics‐based approaches. However, comparative genomics approaches are limited to syntenic inference and recombination is suppressed within the pericentromeric regions of wheat chromosomes, thus, precise ordering of physical maps and sequenced contigs across the whole‐genome using these approaches is nearly impossible. We developed a whole‐genome radiation hybrid (WGRH) resource and tested it by genotyping a set of 115 randomly selected lines on a high‐density single nucleotide polymorphism (SNP) array. At the whole‐genome level, 26 299 SNP markers were mapped on the RH panel and provided an average mapping resolution of approximately 248 Kb/cR1500 with a total map length of 6866 cR1500 . The 7296 unique mapping bins provided a five‐ to eight‐fold higher resolution than genetic maps used in similar studies. Most strikingly, the RH map had uniform bin resolution across the entire chromosome(s), including pericentromeric regions. Our research provides a valuable and low‐cost resource for anchoring and ordering sequenced BAC and next generation sequencing (NGS) contigs. The WGRH developed for reference wheat line Chinese Spring (CS‐WGRH), will be useful for anchoring and ordering sequenced BAC and NGS based contigs for assembling a high‐quality, reference sequence of hexaploid wheat. Additionally, this study provides an excellent model for developing similar resources for other polyploid species. Significance Statement: Anchoring and ordering sequenced contigs in large genomes, such as hexaploid wheat, are challenging tasks; synteny‐based approaches are limited in areas of low recombination. Here we show that single nucleotide polymorphism mapping of radiation hybrids is useful for ordering sequenced contigs throughout the length of any chromosome. This approach should be applicable to other polyploid species.